Serum metabolomics and gut microbiota analysis reveal the lipid-lowering effects of fermented triple-bean soup in high-fat diet-fed mice - Hao, Zina; Li, Xinyi; Li, Zongze; Ma, Menghan; Xi, Yue; Yu, Li; Wang, Yimeng; Zhang, Baogang; Xu, Yunhe; Zhang, Lili (Frontiers in Nutrition, 2025)
Triple-bean soup (TBS), a traditional Chinese functional food, was innovatively fermented with lactic acid bacteria (FTBS) to enhance its hypolipidemic potential. Using a multi-omics approach integrating 16S rRNA sequencing and serum metabolomics, we systematically investigated FTBS’s effects on high-fat diet (HFD)-induced metabolic disorders in mice. FTBS significantly alleviated HFD-induced metabolic disorders, outperforming UFTBS. It remodels the microbial ecosystem by suppressing obesogenic bacteria, restoring microbial diversity and F/B balance, and increasing the abundance of Prevotella, Coprococcus, and Oscillospira. The levels of short-chain fatty acids (SCFAs), notably butyrate and propionate, increased by 1.8-fold following a substantial enrichment of key beneficial bacterial species, including Prevotella and Coprococcus. Metabolomic profiling identified that FTBS modulates the levels of 192 metabolites, reprogrammed key pathways, such as valine, leucine, and isoleucine biosynthesis, glycerophospholipid metabolism, citrate cycle, and primary bile acid biosynthesis. Consequently, systemic metabolomic profiles improved, manifesting as reduced hepatic steatosis and improved blood lipid levels. Our study demonstrates that FTBS ameliorates metabolic syndrome by modulating the gut-liver axis via specific microbial and metabolic shifts. These findings position FTBS as a promising nutraceutical for metabolic liver disease, merging traditional dietary knowledge with modern microbiome science.